Designing the Educational Environment in the Formation of Adaptation and Integration Strategies in Children from Migrant Families - Komarova, N. M.; Suslova, T. F. (International Dialogues on Education Journal, 2022)
This article is devoted to the study of the possibilities of educational environment design in the arrangement of the schoolwork with children from migrant families so that they could positively adapt to the conditions of school and integrate into the culture of the host country. Based on a generalization of the problems faced by migrant children, the characteristics of educational environment design models and technologies, and international experience in developing and designing electronic educational resources, designing the process of teaching and educating children from migrant families, regardless of their social status, the role and place of educational environment design, as well as the conditions and mechanisms of increasing the effectiveness of designing the educational environment of educational and training processes for children from migrant families are outlined. The reasons for the introduction of interactive methods of teaching and educating migrant children, especially during the adaptation period, are outlined. Educational environment design is considered from the position of a systematic approach to the design of the educational process, in which the content, methodology and conditions of the organization are subordinated to a single goal, and the roles of not only teachers, but also the families of migrant children, peers, other people and organizations are defined in this system.